Something old and something new. Techniques to improve the lexical inventory of EST students : a proposal - Miranda García, Antonio; Calle Martín, Javier; Moreno Olallas, David (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2004)
One of the main difficulties encountered by Spanish students of Engineering when they are confronted with a technical text in English lies more often than not in their poor command of the lexicon, both general and subtechnical. It seems obvious that the learning of lengthy wordlists by rote must be discarded as idle, since the students can usually only recall a few items once a few days have passed. This particular tedious learning task can be eased by favouring a set of associations within the learners’ mental lexicon so as to relate a certain word with its designatum, or else to link mentally the word in English with its homologue (or near homologue) in the mother tongue. These associations share the common objective of adding to the learners’ vocabulary through the creation of word-links, both syntagmatically and paradigmatically. In this paper we present some techniques that have proved helpful to our students in building up both their active and passive vocabulary in quantitative and qualitative terms. On the one hand, procedural, word-formation and warm-up activities have been employed so far in the field of EST; etymology, on the other, is more innovative in foreign language teaching.